Creating Future People The Ethics of Genetic Enhancement - Anomaly, Jonathan (Taylor & Francis, 2020)
Creating Future People offers readers a fast-paced primer on how new genetic technologies will enable parents to influence the traits of their children, including their intelligence, moral capacities, physical appearance, and immune system. It deftly explains the science of gene editing and embryo selection, and raises the central moral questions with colorful language and a brisk style. Jonathan Anomaly takes seriously the diversity of preferences parents have, and the limits of public policy in regulating what could soon be a global market for reproductive technology. He argues that once embryo selection for complex traits happens it will change the moral landscape by altering the incentives parents face. All of us will take an interest in the traits everyone else selects, and this will present coordination problems that previous writers on genetic enhancement have failed to consider. Anomaly navigates difficult ethical issues with vivid language and scientifically informed speculation about how genetic engineering will transform humanity. Key features: Offers clear explanations of scientific concepts; Explores important moral questions without academic jargon; Brings discoveries from different fields together to give us a sense of where humanity is headed.